The necessity of data availability in maintaining the value and longevity of paleointensity results - Paterson, Greig A. (Frontiers in Earth Science, 2014)
Asserting the reliability of paleointensity estimates, or comparing relative reliabilities between vastly or subtly different results is a key challenge for paleointensity studies, which often leaves interpretations of these data rife with ambiguities. How we define reliable data is a concept that changes as our understanding of data and experiments advances. As a community we need to take steps to push this forward in an objective fashion that provides the most benefit, not just for paleointensity analysts, but also for those who ultimately wish to use the data to better understand deep Earth processes. However, in this ever-changing landscape, we must also ensure that the data we obtain do not lose their value as our advances threaten to make published data obsolete. It remains unknown exactly how our ability to assess the reliability of data will change and what information will become relevant. It is therefore essential for paleointensity studies to report as much data and meta-data as possible and, ideally, publically archive their measurement data for future reanalysis. Such practices are important, not only for paleointensity studies, but science in general and their implementation is vital to the future of paleomagnetism.